Validation of a canopy photosynthesis model for cocksfoot pastures grown under different light regimes - Peri, Pablo Luis (2006)
Daily net canopy photosynthesis (Pn) was predicted for cocksfoot (Dactylis glomerata L.) canopies grown under different light regimes by integration of a leaf photosynthesis model developed for the light-saturated photosynthetic rate (Pmax), photosynthetic efficiency (a) and the degree of curvature (h) of the leaf light– response curve. When shade was the only limiting factor, the maximum Pn (Pnmax) was predicted to decrease approximately linearly from 33.4 g CO2 mÿ2 dÿ1 to zero as photosynthetic photon flux density (PPFD) fell from full sunlight (1800 lmol mÿ2 sÿ1 PPFD) to 10% of this in a fluctuating light regime. It was also predicted that at 50% transmissivity Pnmax was higher for a continuous light regime (10.4 g CO2 mÿ2 dÿ1) than for a fluctuating light regime with the same intensity (8.4 g CO2 mÿ2 dÿ1). The canopy photosynthesis model was then used to predict dry matter (DM) production for cocksfoot field grown pastures under a diverse range of temperature, herbage nitrogen content and water status conditions in fluctuating light regimes. This prediction required inclusion of leaf area index and leaf canopy angle from field measurements. The model explained about 85% of the variation in observed cocksfoot DM production for a range from 6 to 118 kg DM haÿ1 dÿ1. The proposed model improves understanding of pasture growth prediction through integration of relationships between shade limitations in fluctuating light regimes and other environmental factors that affect the canopy photosynthetic rate of cocksfoot pastures in silvopastoral systems.